2013
DOI: 10.1097/mnh.0b013e3283641a89
|View full text |Cite
|
Sign up to set email alerts
|

Renal nerves in blood pressure regulation

Abstract: The observation that bilateral renal nerve ablation can reduce blood pressure represents an important therapeutic milestone. Nonetheless, questions arise as to the underlying mechanisms, the long-term consequences, whether there may be re-innervation over a number of years, or whether some unknown consequence to the denervation may arise. This may point to the development of novel compounds targeted to the innervation of the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Activation of renal sympathetic nerves plays an important role in the pathogenesis of HTN (119). Renal denervation (RDN) is a percutaneous catheter-based renal sympathetic denervation procedure to disrupt renal afferent and efferent nerves using radiofrequency ablation (120, 123, 124).…”
Section: Perspectivesmentioning
confidence: 99%
“…Activation of renal sympathetic nerves plays an important role in the pathogenesis of HTN (119). Renal denervation (RDN) is a percutaneous catheter-based renal sympathetic denervation procedure to disrupt renal afferent and efferent nerves using radiofrequency ablation (120, 123, 124).…”
Section: Perspectivesmentioning
confidence: 99%
“…). The high‐ and low‐pressure baroreceptors represent one of the most potent afferent inputs which reflexly regulate sympathetic outflow that impacts not only on the cardiovascular system but also on the kidney to determine extracellular fluid volume (Johns & Abdulla ). Impaired baroreflex regulation of renal sympathetic nerve activity (RSNA) has been reported in both diet‐induced and genetically obese rats (Wong & Johns , Skrapari et al .…”
mentioning
confidence: 99%
“…Experimental studies demonstrated that renal denervation slowed or delayed the rise in BP in experimental models of hypertension such as spontaneous hypertension, salt-sensitive hypertension, Nω-nitro-L-arginine methyl ester (L-NAME) induced hypertension, Ang II induced hypertension and deoxycorticosterone acetate (DOCA)-salt hypertension [99][100][101][102][103][104][105]. Singh et al reported that the reduction in BP and albuminuria and improved GFR in sheep with hypertensive CKD, observed at 5 months after catheter-based RDNx, were sustained until 30 months after RDNx, demonstrating the long-term durability of the beneficial effects of RDNx in hypertensive CKD [106].…”
Section: Inactivation Of Ne-ar Signaling In Aki and Ckdmentioning
confidence: 99%